“Atypical” Mild Clinical Presentation in Elderly Patients With Ruptured Intracranial Aneurysm: Causes and Clinical Characteristics - Wen, Dingke; Chen, Ruiqi; Zhang, Tianjie; Li, Hao; Zheng, Jun; Fu, Wei; You, Chao; Ma, Lu (Frontiers in Surgery, 2022)
Objective: Thunderclap-like severe headache or consciousness disturbance is the common “typical” clinical presentation after aneurysmal subarachnoid hemorrhage (aSAH); however, a slowly developing “atypical” clinical pattern, with mild headache, vomiting, or dizziness, is frequently noted in elderly patients. The aim of this study was to evaluate the clinical characteristics of this “atypical” subgroup, as well as related factors associated with the presence of these mild symptoms. Methods: The data of 176 elderly patients (≥70 years old) with ruptured intracranial aneurysms (IAs) treated at our center from January 2016 to January 2020 were retrospectively collected and analyzed. The patients were divided into “typical” and “atypical” groups based on their initial and development of clinical symptoms after the diagnosis of aSAH. Intergroup differences were analyzed, and factors related to the presence of these two clinical patterns were explored through multiple logistic regression analyses. Results: Despite significant admission delay (P<0.001) caused by mild initial symptoms with slow development, patients in the “atypical” group achieved better clinical prognosis, as indicated by a significantly higher favorable outcome ratio and lower death rate upon discharge and at different time points during the 1-year follow-up, than the “typical” group (P<0.05). Multiple logistic regression analysis revealed that modified Fisher grade III-IV (OR=11.182, P=0.003), brain atrophy (OR=10.010, P=0.001), a larger lesion diameter (OR=1.287, P<0.001) and current smoking (OR=5.728, P<0.001) were independently associated with the presence of “typical” symptoms. Aneurysms with wide necks (OR=0.013, P<0.001) were independently associated with the presence of “atypical” symptoms. Conclusions: "Atypical” presentations, with mild clinical symptoms and slow development, were commonly recorded in elderly patients after the onset of aSAH. Despite the prolonged admission delay, these “atypical” patients achieved better clinical outcomes than those with “typical” symptoms. Modified Fisher grade (III-IV), current smoking, brain atrophy and larger lesion diameter were factors predictive of “typical” symptoms, while aneurysms with wide necks were independently associated with “atypical” symptoms.